Sulfur-Based Mixotrophic Denitrification with the Stoichiometric S0/N Ratio and Methanol Supplementation: Effect of the C/N Ratio on the Process - Huilinir-Curio, C; Yanez-Sevilla, D (Taylor and Francis Ltd., 2021)
The impact of the organic carbon to nitrate ratio (C/N ratio) on mixotrophic denitrification rate has been scarcely studied. Thus, this work aims to investigate the effect of the C/N ratio on the mixotrophic denitrification when methanol is used as a source of organic matter and elemental sulfur as an electron donor for autotrophic denitrification. For this, two initial concentrations of NO3--N (50 and 25 mg/L) at a stoichiometric ratio of S0/N, and four initial C/N ratios (0, 0.6, 1.2, and 1.9 mg CH3OH/mg NO3- -N) were used at 25 (±2) °C. The results showed that when using a C/N ratio of 0.6, the highest total nitrogen removal was obtained and the accumulation of nitrites was reduced, compared to an autotrophic system. The most significant contribution to nitrate consumption was through autotrophic denitrification (AuDeN) for a C/N ratio of 0.6 and 1.2, while for C/N = 1.9 the most significant contribution of nitrate consumption was through heterotrophic denitrification (HD). Finally, organic supplementation (methanol) served to increase the specific nitrate removal rate at high and low initial concentrations of substrate. Therefore, the best C/N ratio was 0.6 since it allowed for increasing the removal efficiency and the denitrification rate. © 2021 Taylor & Francis Group, LLC.